Extracellular glucose levels in cultures of undifferentiated mouse trophoblast stem cells affect gene expression during subsequent differentiation with replicable cell line-dependent variation - Kenta NISHITANI; Koji HAYAKAWA; Satoshi TANAKA (The Society for Reproduction and Development, 2018)
Mouse trophoblast stem cells (TSCs) have been established and maintained using hyperglycemic conditions (11 mM glucose) for no apparent good reason. Because glucose metabolites are used as resources for cellular energy production, biosynthesis, and epigenetic modifications, differences in extracellular glucose levels may widely affect cellular function. Since the hyperglycemic culture conditions used for TSC culture have not been fully validated, the effect of extracellular glucose levels on the properties of TSCs remains unclear. To address this issue, we investigated the gene expression of stemness-related transcription factors in TSCs cultured in the undifferentiated state under various glucose concentrations. We also examined the expression of trophoblast subtype markers during differentiation, after returning the glucose concentration to the conventional culture concentration (11 mM). As a result, it appeared that the extracellular glucose conditions in the stem state not only affected the gene expression of stemness-related transcription factors before differentiation but also affected the expression of marker genes after differentiation, with some line-to-line variation. In the TS4 cell line, which showed the largest glucose concentration-dependent fluctuations in gene expression among all the lines examined, low glucose (1 mM glucose, LG) augmented H3K27me3 levels. An Ezh2 inhibitor prevented these LG-induced changes in gene expression, suggesting the possible involvement of H3K27me3 in the changes in gene expression seen in LG. These results collectively indicate that the response of the TSCs to the change in the extracellular glucose concentration is cell line-dependent and a part of which may be epigenetically memorized.